(untitled) (Proceedings of Southern Federal University. Philology, 2015)
This article describes the special epistolary genre - a genre of “letters to the leader”; it briefly analyzes the letter of declaration by Alexander Solzhenitsyn “Letter to the Leaders of the Soviet Union” (a kind of “lesson for tsars”) and his polemic with R.A. Medvedev concerning the text. Solzhenitsyn and Medvedev are different in their views on the current ideology, the national problem in the democratization of the country, on religion, on the nature of Marxism, on the military-industrial complex and the threat of war on the fate of the Russian people in the XX century, on the technical and economic progress and the planet’s resources. Despite the fact that Medvedev agrees with some private aspects of Solzhenitsyn, in general he evaluates the “Letter to the Leaders of the Soviet Union” as an extremely negative and realizing the scale of the Solzhenitsyn’s individual he believes that he adheres to the backward views. Solzhenitsyn serves as a believer, Medvedev - as a Marxist and an atheist. We have also considered the perception of controversy of Solzhenitsyn and Medvedev by M.Agursky. He believes that Solzhenitsyn criticized Marxism in principle that denies the moral and concludes that “over time, the view expressed by Solzhenitsyn, will gain more and more supporters, despite the fact that small number of people share it”. The article by Agursky reflected high evaluation of “Letters” by Solzhenitsyn, recognition of the importance of this text for understanding the fate of Russia in the past and in the present. Key words: epistolary literature, “the letter to the leader,” Russian literature, censorship, literature and power, Alexander Solzhenitsyn, R.A. Medvedev. Surovtseva Ekaterina Vladimirovna - Moscow state university of M.V. Lomonosov, faculty of philology, laboratory of general and computer lexicology and lexicography. Candidate of linguistics, professor of Russian academy of natural science, senior scientific worker. E-mail: surovceva- ekaterina@yandex.ru